Bacterial contamination and its Susceptibility in intensive care unit in Thi-qar province / Iraq - Nasser, Nazar (University of Thi-Qar Journal of Science, 2019)
To identify the cause and the source of bacterial infection among patients of intensive care unit this study had been conducted in Al-Imam Al-Hussein hospital in Thi-qar province for the period from 1st September to end of December 2011 . A total of 320 swabs and samples were collected from 17 different sites of Intensive Care Unit environment and inoculated on a normal cultural media ,then incubated at 37OC for 24 hour . The growth revealed different bacterial colonies which had been tested for their morphological and biochemical characteristics. Sixty eight of pure isolates were obtained including 24 (35.29%) Gram positive bacterial isolates, 44(64.71%) of Gram negative bacterial isolates, the highest rates (19.11%) of bacterial contamination had been found on the walls and the floor . Sensitivity tests for all isolates were done using 25 types of commonly used antibiotics in Iraq, the results revealed that the genus Enterobacter spp. had a high resistance as a Gram negative bacteria, and Staphylococcus spp. had a high resistance as a Gram positive bacteria to most of the tested antibiotics, MIC tests for 5 types of antibiotics were applied on the most resistant and the most sensitive isolates which reflect that all isolates have a low rate of MIC against Ciprofloxacin .